Clear cell carcinoma, not otherwise specified/hyalinising clear cell carcinoma of the salivary gland: The current nomenclature, clinical/pathological characteristics and management. (June 2016) - Daniele, Luca; Nikolarakos, Dimitrios; Keenan, Jonathon; Schaefer, Nathan; Lam, Alfred King-yin
Highlights: Hyalinising clear cell carcinoma (HCCC) noted often in woman, in the seventh decade of life. EWSR1-ATF1 fusion is specific for the carcinoma. 9% of the reported cases had local nodal metastasis. Distant metastatic spread often affected the lung, followed by bone. 22% of patients had recurrent or with persistent diseases after surgery. Abstract: Clear cell carcinoma, not otherwise specified (NOS)/hyalinising clear cell carcinoma (HCCC) is a rare entity in salivary gland tumour. The aim of the research is to review the current concepts and characteristics of this carcinoma. The clinical and pathological data of the disease obtained from literature and two original cases were analysed. Overall, 152 cases were reviewed up to the year 2014. The carcinomas were noted often in woman, in the seventh decade of life, located in oral cavity and as early-stages cancers. On pathological examination, they were characterized by tumour cells having clear cell morphology with hyalinised stroma. Immunohistochemical studies revealed that the carcinoma is positive for cytokeratin and negative for myoepithelial differentiation. EWSR1-ATF1 fusion is specific for the carcinoma. Also, 9% of the reported cases had local nodal metastasis, with 6 cases demonstrating distant metastases at presentation. On follow-up, 22% of patients had recurrent or with persistent diseases after surgery. The time for the first recurrence could be as long as 24 years. Risk factors for recurrence include advanced stage at diagnosis and metastases at presentation. To conclude, HCCC is a low grade malignancy but have the potential for local metastases, recurrence, distant metastases and cancer-related death.